Cytotoxic T cell recognition of Epstein-Barr virus-infected B cells. II. Blocking studies with monoclonal antibodies to HLA determinants. - Wallace, L; Moss, D; Rickinson, AB; Mcmichael, A; Epstein, M (1981)
Monoclonal antibodies specifically binding common determinants on all HLA-A, B anc C antigen molecules blocked the lysis of EB virus-transformed target cells by EB virus-specific cytotoxic T cells reactivated in vitro. Blocking was mediated through binding of the antibodies to the target rather than to the effector cells and was maximal (75 to 85% inhibition of lysis) at saturating antibody concentrations. A similar blocking effect was also shown by a monoclonal antibody binding to beta 2-microglobulin, a molecule physically associated with HLA-A, B and C antigens on the target cell surface, but not by a monoclonal antibody binding to the non-HLA-associated leukocyte-common antigen. Saturating concentrations of monoclonal antibodies specific for common determinants on all HLA-DRw antigen molecules either had no effect at all upon EB virus-specific T cell cytotoxicity or caused a slight, but nonspecific, inhibition. The results demonstrate unequivocally that HLA-A, B and C antigens on the target cell surface are indeed the polymorphic elements which impose genetic restriction upon EB virus-specific cytotoxic T cell function.